A comprehensive two-sample Mendelian randomization analysis of trigeminal neuralgia and modifiable risk factors - Wei, Xingrong; Zhou, Hao; Zhang, Shuguang; Hu, Xueqian; Wei, Zhenqin; Li, Yang (Frontiers in Neurology, 2023)
Objective To conduct a comprehensive search and causality study of potential modifiable risk factors for trigeminal neuralgia. To provide new ideas for subsequent treatment and management of patients with trigeminal neuralgia. Methods Data were obtained from large GWAS databases and then analyzed by Mendelian randomization analysis. The causal relationship between 36 potentially modifiable risk factors and trigeminal neuralgia was explored based on the results of the inverse variance weighting method(IVW). p < 0.05 was considered statistically significant. Results Years of schooling [OR (95%CI), 0.59(0.42–0.84), p = 0.003] to be a significant protective factor. Anxiety disorders [OR (95%CI), 1.62(1.05–2.48), p = 0.028], Depression [OR (95%CI), 1.53(1.03–2.28), p = 0.035] and Autoimmune [OR (95%CI), 1.16(1.01–1.32), p = 0.033] were significant risk factors. Sleep duration [OR (95%CI), 0.43(0.18–1.01), p = 0.051] was a close protective factor. Body mass index [OR (95%CI), 1.24(0.98–1.57), p = 0.077] was a close risk factor. Conclusion Mendelian randomization analysis shows Years of schooling and Sleep duration as protective factors. Anxiety disorders, Depression, Autoimmune, and Body mass index are risk factors. This will help in the research of diagnosis, treatment, and mechanism of trigeminal neuralgia. And reduce the prevalence of trigeminal neuralgia through positive psychological and lifestyle interventions.